Measuring the burden of disease using disability-adjusted life years in Shilin County of Yunnan Province, China - Zhou, Shang-Cheng (Springer Japan, 2010)
BACKGROUND: Few studies calculating burden of disease (BOD) have been carried out in China. Disability-adjusted life years (DALY) is one of the useful methods used to estimate BOD. This study aims to use DALY for evaluating BOD and to provide useful information for health planning for residents in Shilin Yi Nationality Autonomous County (Shilin County) of Yunnan Province, China. METHODS: Methods developed for the Global Burden of Disease (GBD) Study by the World Bank and World Health Organization (WHO) were adapted and applied to Shilin County population health data. DALY rate per 1,000 was calculated from medical death certificates in 2003 in Shilin County. The geographic coordinates of towns or townships were determined using the geocode function of R2.3.1 geographical information system (GIS) software. RESULTS: Respiratory diseases were by far the leading cause of years of life lost (YLL) in both males and females. The four other leading causes of YLL in descending order were: unintentional injuries, cardiovascular diseases, intentional injuries, and malignant neoplasms. However, the five leading causes of years lived with disability (YLD) were, in descending order: neuropsychiatric conditions, intentional injuries, respiratory diseases, unintentional injuries, and cardiovascular diseases. The leading cause of total disease burden (DALY) was neuropsychiatric conditions. Townships of Muzhuqing, Xijiekou, and Weize were the areas with most serious disease burden in Shilin County. CONCLUSIONS: Prevention and treatment of neuropsychiatric conditions and respiratory diseases for both females and males should be enhanced in Shilin County, so as to decrease injury. More preventive interventions for noninfectious chronic diseases should be emphasized in remote townships.